Analisis Nilai Tambah Pengolahan Gabah Menjadi Beras Desa Tampabulu Kecamatan Poleang Utara Kabupaten Bombana - Saputra, I Kadek Ari; Bafadal, Azhar; Taridala, Sitti Aida Adha (Department of Agribusiness, Halu Oleo University, 2019)
Putra Doping is the rice milling industry in activities using technology and processing tools. With technologies, tranformatiomÂ raw material (paddy) low value to be rice. The purpose of this research is to analyze of the value-added and distribution in the businesses of paddy processing become rice in Tampabulu Village, North Poleang Subdistrict, Bombana District. This processing is done on March 2017-April 2019.Â The determination of the research area based on the consideration, is that Putra Doping is the biggest business in Tampabulu. The respondents in this research is the owner of rice milling Putra Doping businesses. The analysis method that used are the value-added Hayami. The result of this research showed that the businesses of paddy processing to become rice give the value-added as Rp 635,4/kg paddy. Distribution of value added to be company profit as Rp 495,4 and labor compensation as Rp 140